Super-hydrophobic anti-fouling lubricating grease
By modifying ZnO particles with fluorosilane and in-situ growing SiO2 nanoparticles to form a multi-level hydrophobic structure, the failure problem of grease in humid and polluted environments is solved, efficient hydrophobicity and stability are achieved, and the life of the equipment is extended.
Patent Information
- Application Number
- CN202510815411.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-10-10
AI Technical Summary
Existing superhydrophobic greases are prone to degradation of their hydrophobic properties in mechanical equipment due to mechanical shear or high-temperature aging, and the poor compatibility of the internal components of the grease leads to failure in humid and polluted environments, affecting the life and reliability of the equipment.
Fluorosilane-modified ZnO particles are used to in situ grow SiO2 nanoparticles and perform secondary modification to form a multi-level hydrophobic structure, thereby enhancing the hydrophobic properties of the grease. SiO2 nanoparticles are grown in situ on the surface of ZnO@fluorosilane particles, and then fluorosilane modification is performed on the surface of the SiO2 nanoparticles to form primary, secondary and tertiary hydrophobic structures, thereby improving the stability and anti-fouling ability of the grease.
The initial hydrophobic contact angle of the grease exceeds 150°, and the hydrophobicity decays slowly under dynamic friction and humid environments, effectively repelling water and pollutants, reducing the risk of emulsification failure, protecting metal surfaces, and extending equipment life.
Smart Images

Figure BDA0005455088300000071 
Figure BDA0005455088300000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubricating grease, and in particular relates to a super-hydrophobic anti-fouling lubricating grease. Background Art
[0002] As a semi-solid lubricating material, grease performs multiple functions in mechanical equipment, including lubrication, sealing, corrosion protection and shock absorption. Its core function is to form a protective film by adhering to the friction surface, thereby reducing direct contact and wear between metals.
[0003] As industrial technology expands into extreme environments (such as deep sea, polar regions, and chemical corrosion scenarios) and precision fields, the performance shortcomings of traditional greases under complex working conditions are gradually exposed, especially in environments with high humidity, multiple pollutants, or frequent contact with liquids. Problems such as water intrusion, lubricant emulsification failure, and surface contamination seriously restrict equipment life and operational reliability. In this context, the research on superhydrophobic greases has become an important direction in the field of lubricating materials. It not only needs to inherit the friction-reducing and anti-wear properties of traditional greases, but also needs to give the material extremely strong hydrophobicity (contact angle > 150°) through surface chemical modification or structural design to repel water, corrosive media, and pollutants, thereby solving problems such as lubrication failure, metal corrosion, and dirt deposition in humid environments. However, existing superhydrophobic grease technology still faces multiple challenges: First, the superhydrophobic function often relies on micro-nano rough structures constructed by fluorinated compounds or nanoparticles, but such materials are prone to structural damage due to mechanical shear or high-temperature aging, and the hydrophobic performance decays rapidly; second, the compatibility contradictions between the complex components inside the grease (such as thickeners and additives) and the hydrophobic modifiers are prominent, which can easily cause phase separation or decreased stability.
[0004] Therefore, developing a grease system with long-lasting superhydrophobicity and adaptability to multiple working conditions has become an important research topic to improve the reliability of high-end equipment and promote green manufacturing. Summary of the Invention
[0005] In view of this, the object of the present invention is to provide a super hydrophobic and anti-fouling grease. The initial hydrophobic contact angle of the grease of the present invention exceeds 150°, which is significantly higher than that of traditional greases and can effectively repel water, corrosive media and pollutants.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a super-hydrophobic anti-fouling grease, comprising the following raw materials in parts by weight:
[0008] 60-70 parts of base oil, 10-20 parts of thickener, 1-3 parts of antioxidant, 1-3 parts of rust inhibitor, 3-5 parts of anti-wear hydrophobic compound agent;
[0009] The anti-wear hydrophobic composite agent is made of fluorosilane-modified ZnO surface loaded with fluorosilane-modified SiO2.
[0010] Preferably, the base oil is one or both of mineral oil and polyalphaolefin synthetic oil.
[0011] Preferably, the thickener is one or more of fatty acid, dibasic acid, alkoxy titanium, and composite aluminum-based thickener.
[0012] Preferably, the antioxidant is one or more of zinc dialkyl dithiophosphate, zinc alkyl dithiocarbamate, and phenyl α-naphthylamine dialkyl diphenylamine.
[0013] Preferably, the rust inhibitor is one of alkylbenzene sulfonate, long-chain organic carboxylic acid, and sorbitan oleate.
[0014] Preferably, the preparation method of the anti-wear hydrophobic composite agent is:
[0015] (1) ZnO particles were immersed in a fluorosilane ethanol solution, ultrasonically treated, and then filtered and dried to obtain ZnO@fluorosilane particles;
[0016] (2) Dispersing ZnO@fluorosilane particles in ethyl orthosilicate ethanol solution and then adding ammonia water to adjust the pH to 9-10 and stirring for 12-24 hours to obtain ZnO@fluorosilane-SiO2 particles;
[0017] (3) The ZnO@fluorosilane-SiO2 particles were ultrasonically treated in a fluorosilane ethanol solution and then filtered and dried to obtain an anti-wear hydrophobic composite.
[0018] Preferably, the ZnO particles in step (1) have a particle size of 1-10 μm.
[0019] Preferably, the ultrasonication time in step (1) is 30 to 60 minutes.
[0020] Preferably, the drying temperature in step (1) is 60-70°C.
[0021] Currently, ZnO and other particles are commonly used as extreme pressure anti-wear agents in greases. However, ZnO itself is a hydrophilic material, which can easily cause the grease to contain a large amount of water in a humid environment, causing the grease to lose its lubricating effect and corrode equipment. The present invention overcomes the above problem by modifying the ZnO particles with fluorosilane to make their surface hydrophobic.
[0022] Preferably, the concentration of the fluorosilane ethanol solution in step (2) is 1-5 wt%;
[0023] The fluorosilane is one of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane and heptadecafluorodecyltrimethoxysilane.
[0024] Preferably, the concentration of the ethyl orthosilicate ethanol solution in step (1) and step (3) is independently 5 to 10 wt%.
[0025] Preferably, the SiO2 particle size in the ZnO@fluorosilane-SiO2 particles is 10 to 20 nm.
[0026] The present invention also found that the current use of hydrophobic modified particles to increase the hydrophobicity of grease has achieved certain results, but the hydrophobic performance needs to be improved. During use, the hydrophobicity gradually disappears due to factors such as friction, and the hydrophobicity time is short. The present invention in situ grows SiO2 nanoparticles on the surface of ZnO@fluorosilane particles, and then performs fluorosilane modification on the surface of the SiO2 nanoparticles. In this method, the fluorosilane modification of the surface of the SiO2 nanoparticles forms a primary hydrophobic structure, and the SiO2 nanoparticles form an irregular rough interface on the ZnO surface to form a secondary hydrophobic structure, and the fluorosilane-modified ZnO forms a tertiary hydrophobic structure. The primary hydrophobic structure utilizes the properties of the hydrophobic modification layer to be hydrophobic. The secondary hydrophobic structure utilizes the hydrophobicity of the material itself, and the roughened surface can further enhance the hydrophobicity by increasing the actual contact angle. The tertiary hydrophobic structure can also have hydrophobic properties in the part of the ZnO surface where SiO2 nanoparticles are not generated. At the same time, during use, the ZnO sites exposed by the shedding of nano-SiO2 are also modified sites through fluorosilane, so that the hydrophobic function can be sustained.
[0027] Contains at least the following beneficial technical effects:
[0028] The initial hydrophobic contact angle of the grease of the present invention exceeds 150°, which is significantly higher than that of traditional greases and can effectively repel water, corrosive media and pollutants. Through the multi-level hydrophobic structure design, the hydrophobicity of the grease decays slowly under dynamic friction or humid environments. The hydrophobic structure reduces the intrusion of moisture and pollutants, reduces the risk of grease emulsification failure, and protects the metal surface from corrosion, thereby extending the life of the equipment. The anti-wear hydrophobic composite agent solves the compatibility problem between traditional hydrophobic agents and grease components through a step-by-step modification process (in-situ growth of SiO2 nanoparticles on the surface of ZnO@fluorosilane particles and secondary modification), avoiding phase separation or performance degradation. In complex environments such as high humidity and multiple pollutants (such as deep sea and chemical scenes), the grease can still maintain stable lubrication performance and meet the stringent requirements of high-end equipment. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the present invention. The present description and examples are intended to be illustrative only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] Unless otherwise specified, the "room temperature" and "normal temperature" mentioned in the present invention are all calculated as 25±2°C.
[0035] Unless otherwise specified, all raw materials and instruments used in the following examples of the present invention are commercially available.
[0036] Example 1
[0037] Preparation of anti-wear hydrophobic composite:
[0038] (1) ZnO particles with a particle size of 5 μm were immersed in a 3 wt % tridecafluorooctyltriethoxysilane ethanol solution and ultrasonically treated for 45 min, then filtered and dried at 65°C to obtain ZnO@fluorosilane particles;
[0039] (2) Disperse ZnO@fluorosilane particles in 8 wt% ethyl orthosilicate ethanol solution, then add ammonia water to adjust the pH to 9 and stir the reaction for 16 h to obtain ZnO@fluorosilane-SiO2 particles; the SiO2 particles have a particle size of 15 nm.
[0040] (3) The ZnO@fluorosilane-SiO2 particles were ultrasonically treated in a 3 wt% tridecafluorooctyltriethoxysilane ethanol solution for 45 min, and then filtered and dried at 65 °C to obtain an anti-wear hydrophobic composite.
[0041] Preparation of superhydrophobic antifouling grease:
[0042] Weigh the base oil PAO 40 (viscosity 40.28 mm at 100 ° C) by weight. 2 / s), 65 parts of a composite aluminum-based thickener, 15 parts of an alkyl dithiocarbamate zinc, 2 parts of anhydrous sorbitan oleate, and 4 parts of an anti-wear hydrophobic composite agent were mixed together in a mixer at 60° C. to obtain a super hydrophobic and anti-fouling grease.
[0043] Example 2
[0044] Preparation of anti-wear hydrophobic composite:
[0045] (1) ZnO particles with a particle size of 1 μm were immersed in a 1 wt% ethanol solution of heptadecafluorodecyltrimethoxysilane and ultrasonically treated for 30 min, then filtered and dried at 6°C to obtain ZnO@fluorosilane particles;
[0046] (2) Disperse ZnO@fluorosilane particles in 5 wt% ethyl orthosilicate ethanol solution, then add ammonia water to adjust the pH to 9 and stir the reaction for 12 h to obtain ZnO@fluorosilane-SiO2 particles; the SiO2 particles have a particle size of 10 nm.
[0047] (3) The ZnO@fluorosilane-SiO2 particles were ultrasonically treated in a 1 wt% tridecafluorooctyltriethoxysilane ethanol solution for 30 min, and then filtered and dried at 65 °C to obtain an anti-wear hydrophobic composite.
[0048] Preparation of superhydrophobic antifouling grease:
[0049] Weigh MVI650 oil (viscosity 13.73 mm at 100 °C) by weight. 2 / s), 60 parts of a composite aluminum-based thickener, 10 parts of a dialkyl zinc dithiophosphate, 1 part of an alkylbenzene sulfonate, and 3 parts of an anti-wear hydrophobic composite agent were mixed uniformly in a mixer at 60° C. to obtain a super hydrophobic and anti-fouling grease.
[0050] Example 3
[0051] Preparation of anti-wear hydrophobic composite:
[0052] (1) ZnO particles with a particle size of 10 μm were immersed in a 5 wt% tridecafluorooctyltriethoxysilane ethanol solution and ultrasonically treated for 60 min, then filtered and dried at 70°C to obtain ZnO@fluorosilane particles;
[0053] (2) Disperse ZnO@fluorosilane particles in 10 wt% ethyl orthosilicate ethanol solution, then add ammonia water to adjust the pH to 10 and stir for 24 h to obtain ZnO@fluorosilane-SiO2 particles; the SiO2 particles have a particle size of 20 nm.
[0054] (3) The ZnO@fluorosilane-SiO2 particles were ultrasonically treated in a 5 wt% tridecafluorooctyltriethoxysilane ethanol solution for 60 min, and then filtered and dried at 70°C to obtain an anti-wear hydrophobic composite.
[0055] Preparation of superhydrophobic antifouling grease:
[0056] Weigh the base oil (viscosity 40.28 mm at 100 °C) by weight. 2 / s, viscosity at 100℃ is 13.73mm 2 / s prepared in a 1:1 ratio, 70 parts of a composite aluminum-based thickener, 20 parts of a phenyl α-naphthylamine dialkyl diphenylamine, 3 parts of anhydrous sorbitan oleate, and 5 parts of an anti-wear hydrophobic composite agent were mixed together in a mixer at 60° C. to obtain a super hydrophobic and anti-fouling grease.
[0057] Comparative Example 1
[0058] Preparation of anti-wear hydrophobic composite:
[0059] (1) ZnO particles with a particle size of 5 μm were immersed in a 3 wt % tridecafluorooctyltriethoxysilane ethanol solution and ultrasonically treated for 45 min, and then filtered and dried at 65° C. to obtain an anti-wear hydrophobic composite.
[0060] Preparation of superhydrophobic antifouling grease:
[0061] Weigh the base oil PAO 40 (viscosity 40.28 mm at 100 ° C) by weight. 2 / s), 65 parts of a composite aluminum-based thickener, 15 parts of an alkyl dithiocarbamate zinc, 2 parts of anhydrous sorbitan oleate, and 4 parts of an anti-wear hydrophobic composite agent were mixed together in a mixer at 60° C. to obtain a super hydrophobic and anti-fouling grease.
[0062] Comparative Example 2
[0063] Preparation of anti-wear hydrophobic composite:
[0064] ZnO particles with a particle size of 5 μm were immersed in a 3 wt% tridecafluorooctyltriethoxysilane ethanol solution and ultrasonically treated for 45 min, then filtered and dried at 65°C to obtain ZnO@fluorosilane particles;
[0065] SiO2 with a particle size of 15 nm was placed in a 3 wt% tridecafluorooctyltriethoxysilane ethanol solution and ultrasonically treated for 45 min to obtain SiO2@fluorosilane particles.
[0066] ZnO@fluorosilane particles and SiO2@fluorosilane particles were mixed in a mass ratio of 10:3 to obtain an anti-wear hydrophobic composite.
[0067] Preparation of superhydrophobic antifouling grease:
[0068] Weigh the base oil PAO 40 (viscosity 40.28 mm at 100 ° C) by weight. 2 / s), 65 parts of a composite aluminum-based thickener, 15 parts of an alkyl dithiocarbamate zinc, 2 parts of anhydrous sorbitan oleate, and 4 parts of an anti-wear hydrophobic composite agent were mixed together in a mixer at 60° C. to obtain a super hydrophobic and anti-fouling grease.
[0069] Experimental Example 1
[0070] 1. Hydrophobicity test
[0071] Blank control: weigh the base oil PAO 40 (viscosity 40.28 mm at 100 ° C) 2 / s), 65 parts of a composite aluminum-based thickener, 15 parts of a composite aluminum-based thickener, 2 parts of zinc alkyl dithiocarbamate, and 2 parts of sorbitan oleate were mixed together in a mixer at 60° C. to obtain a superhydrophobic anti-fouling grease.
[0072] The lubricating greases prepared in the examples and comparative examples were coated on a 10*10 cm stainless steel plate to a thickness of 200 μm, and the hydrophobic angle was measured (contact angle meter Krüss DSA100), as shown in Table 1.
[0073] Table 1
[0074]
[0075] 2. Dynamic hydrophobicity testing in humid environments
[0076] A deep groove ball bearing (6204, inner diameter 20mm) was coated with 20g of grease and then operated at 1000rpm at 25°C. The moisture content of the grease was tested after 24h, 48h, and 72h. The test results are shown in Table 2. (The grease composition is the same as above)
[0077] The test results are shown in Table 2.
[0078]
[0079] The above experiments show that the grease prepared in the examples of the present invention has good hydrophobicity and durability; the grease prepared in comparative examples 1 to 2 has an initial hydrophobicity close to that of the examples, but the hydrophobicity decreases significantly after long-term use.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A super hydrophobic anti-fouling grease, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of base oil, 10-20 parts of thickener, 1-3 parts of antioxidant, 1-3 parts of rust inhibitor, 3-5 parts of anti-wear hydrophobic compound agent; The anti-wear hydrophobic composite agent is made of fluorosilane-modified ZnO surface loaded with fluorosilane-modified SiO2.
2. The super hydrophobic anti-fouling grease according to claim 1, characterized in that The base oil is one or both of mineral oil and polyalphaolefin synthetic oil.
3. The super hydrophobic anti-fouling grease according to claim 1, characterized in that The thickener is one or more of fatty acid, dibasic acid, alkoxy titanium, and composite aluminum-based thickener.
4. The super hydrophobic anti-fouling grease according to claim 1, characterized in that The antioxidant is one or more of zinc dialkyl dithiophosphate, zinc alkyl dithiocarbamate, and phenyl α-naphthylamine dialkyl diphenylamine.
5. The super hydrophobic anti-fouling grease according to claim 1, characterized in that: The rust inhibitor is one of alkylbenzene sulfonate, long-chain organic carboxylic acid and sorbitan oleate.
6. The super hydrophobic anti-fouling grease according to claim 1, characterized in that The preparation method of the anti-wear hydrophobic composite agent is: (1) ZnO particles were immersed in a fluorosilane ethanol solution, ultrasonically treated, and then filtered and dried to obtain ZnO@fluorosilane particles; (2) Dispersing ZnO@fluorosilane particles in ethyl orthosilicate ethanol solution and then adding ammonia water to adjust the pH to 9-10 and stirring for 12-24 hours to obtain ZnO@fluorosilane-SiO2 particles; (3) The ZnO@fluorosilane-SiO2 particles were ultrasonically treated in a fluorosilane ethanol solution and then filtered and dried to obtain an anti-wear hydrophobic composite.
7. The super-hydrophobic anti-fouling grease according to claim 6, characterized in that: The particle size of the ZnO particles in step (1) is 1-10 μm.
8. The super hydrophobic anti-fouling grease according to claim 6, characterized in that The drying temperature in step (1) is 60-70°C.
9. The super hydrophobic anti-fouling grease according to claim 6, characterized in that: The concentration of the fluorosilane ethanol solution in step (2) is 1-5 wt%; The fluorosilane is one of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane and heptadecafluorodecyltrimethoxysilane.
10. The super hydrophobic anti-fouling grease according to claim 6, characterized in that: The concentration of the ethyl orthosilicate ethanol solution in step (1) and step (3) is independently 5 to 10 wt %.